The Influence of Brand Ambassador Laudya Cinthya Bella's Personality in Sunsilk Clean and Fresh Advertisements on Television on Product Selection Decisions - Widyastuti (Jurnal Mantik, 2022)
The selection of a Brand Ambassador in promoting a product is very important, considering this is a strategic step for manufacturers to make their products the first choice of consumers. The selection of Brand Ambassadors must of course be adjusted between the products offered according to the personality or personality of the Brand Ambassador. The discrepancy between the type of product and the personality of the Brand Ambassador will affect the consumer's image of the product.The purpose of this study is to find out the strength of the characteristics of Brand Ambassadors in determining product choices. The research method is a survey using a questionnaire as a data collection instrument. The results showed that there was a very strong correlation (correlation coefficient 0.908), positive and significant from Laudya Cithya Bella's personality as a Brand Ambassador with product selection decisions for hijab-wearing teenagers in Jakarta. The results of this study also show that Personality Brand Ambassadors influence 82.5% of decisions to choose the products offered so that in the end consumers choose Sunsilk Clean and Fresh. As a celebrity, Laudya Cithya Bella is considered appropriate and able to represent the Sunsilk Clean and Fresh shampoo products offered to teenage consumers.